Phaeoclavulina pseudozippelii sp. nov. (Gomphales, Basidiomycota) from northern Thailand - Nopparat Wannathes (2018)
© 2018 Magnolia Press. Coral fungi in Phu Hin Rong Kla National Park, Thailand, were surveyed from June to September of 2011 and 2012. A novel species, Phaeoclavulina pseudozippelii is described together with illustrations, photographs, and a comparison with phenetically similar taxa. Its taxonomic position was confirmed through phylogenetic analyses of the large subunit and internal transcribed spacer (ITS1-5.8S-ITS2) ribosomal DNA sequences.